Women's perceptions of their right to choose the place of childbirth : an integrative review - Hadjigeorgiou, Eleni; Kouta, Christiana; Papastavrou, Evridiki; Papadopoulos, Irena; Mårtensson, Lena B (My University, 2012)
Objective to provide a critical synthesis of published research concerning women's experiences in choosing where to give birth. Method an integrative literature review was conducted using three databases (MEDLINE, CINAHL and Ovid) for 1997–2009. Inclusion criteria were: (1) publication in the English language; (2) research article; (3) focus on women's perceptions for their birthplace choices; and (4) data collected during pregnancy, at birth and post partum. Findings twenty-one research-based papers met the inclusion criteria, and these used a range of approaches and methods. Four themes were derived from the data: choice of birthplace and medicalisation of childbirth; the midwifery model of care and the rhetoric of birthplace choices; perceptions of safety shaped women's preferences; and choice is related to women's autonomy. Conclusion there is considerable evidence that women worldwide wish to be able to exercise their rights and make informed choices about where to give birth. The medical model remains a strong and powerful influence on women's decisions in many countries. The midwifery model offers birthplace choices to women, while policies and culture in some countries affect midwifery practise. Perceptions of safety shaped women's preferences, and women's autonomy facilitated birthplace choices. Implications for practise these findings can be seen as a challenge for health professionals and policy makers to improve perinatal care based on women's needs. Local research is advisable due to cultural and health system differences.
Keywords: Birthplaces; Women; Women's perceptions